Subtitling and loss of meaning: politeness features in Pieces d'identite/ID - Allen, Atanga Anyele (My University, 2009)
Introduction This research focuses on subtitling as a discipline in translation studies and investigates the extent to which constraints in subtitling lead to loss in meaning, in particular loss of politeness features in the film Pièces d’identité/ID (1998) by Ngangura because of differences in the expression of politeness in French and English which are two opposing cultures. For the past two decades, there has been a growing awareness of African cultural values across the African continent and the African Diaspora as expressed through language. The desire to express those cultural values has led to what is termed “Afritude”1 in Cameroon and other French-speaking West and Central African countries. The spirit of Afritude has long had a tremendous impact on the way Africans consider their cultures and cultural values. The pride in their expression has greatly revolutionised the show business sector: African designers are creating wears that reflect Africanness; musicians are creating and or modernising African musical genres (Makossa, Kwaito, Dombolo, Kwassa-kwassa, etc.); writers are moving from postcolonial themes to other themes which highlight African cultures and values, and finally, film producers and writers are today some of the pioneers of Afritude in the Multimedia sector. Multimedia input in the film industry, through advertisements and the screening of films, further enforced by the relentless activities of FESPACO2 in the promotion of African films and documentaries, has led to an increase in the demand for African films across the continent and beyond. However, between the demand and supply of these films lies the aspect of language barriers created by the huge variety of 1 This refers to the pride to be African and to consume African as expressed by individuals in Cameroon and Gabon, through their preference for African designs, music, dances, and films among others, over those from the Western World. In South Africa the term afrocentrism is used to express this reality. This term was used during the early 1990s till when I left Cameroun and Gabon around mid 2001. The closest synonym to the term Afritude is Afrocentrism as used in South Africa (Personal Experience). 2 Festival Panafricain du Cinéma et de la Télévision de Ouagadougou/ Panafrican Film and Television Festival of Ouagadougou. 2 languages spoken by prospective audiences and consumers. Hence, if the demand for those films is to be met they have to be translated. Film translation is a mode of translation which takes place in four different forms: Voice-over, dubbing, surtitling and subtitling. Voice-overs and dubbing are isosemiotic forms of translation which involve translating speech into speech while diasemiotic forms like surtitling and subtitling have to represent the speech from the soundtrack of the film in writing, usually posted as captions at the bottom of the screen (Hatim and Mason 2000:430). This research focuses on subtitling and shows how constraints in subtitling (linguistics, cultural and technical) have in many ways affected the writing of subtitles in films, and how these constraints have led to loss of meaning, in particular in relation to politeness features, in scenes depicting interpersonal interactions between characters in the film Pièces D’identité/ID.